Histological evaluation of kidney development in young rats after a surgery and management of wound with fibrin glue - Pańczyszyn, Dariusz; Kroll, Paweł; Jagielska, Joanna; Tabaczewski, Piotr; Grochowalski, Marcin; Żurawski, Jakub (Journal of Medical Science, 2018)
Aim. The subject of this study is evaluation of histological hallmarks of kidney growth in rats after a surgery and subsequent management of the wound with fibrin glue. Material and Methods. Sixty-five Wistar rats underwent a surgical procedure resulting in parenchymal injury by incision followed by an application of fibrin glue. Kidneys have been examined and evaluated histologically after 4 weeks (group I) and 26 weeks (group II) after the surgery Results. When fibrin glue was used, in both groups, regular anastomoses of the wound edges of the kidney after surgery were noted. Histological features of kidney growth (renal glomeruli, renal tubules and blood vessels) were observed in the parenchyma and in the postoperative scar. In the second group kidneys grew on average by 3.5mm in the longitudinal section and by 1.89 in the cross section. In this group, the number of renal glomeruli nearly doubled. Glomeruli and tubules were also found in the postoperative scar.
Keywords: kidney; histology; surgery